(3Gdedci aj WH Gdedhcs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3aGYde Cf Yde GdWH eWdhH TQYkG Ydi SHjd GdcaGjI hbO bUOJ ai gPG GdcJGH PcQ eG SCd Yfg Ph GdbQfjf YdeGA GdaQS hGdgfO hGdQhe s
(3BNQgG (B:s
(3gPG BNQ eG bUOfGg hMQQfGg hGYJeOfGg ef GdCOhjI , hGddg GdTGai hGdeYGai s
(3YdjgG Jedc HGSe CMeO Hf eMeO HGbQ GdMHQ ai SfI (B1252s
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B2 - (3U (B49 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B249 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B227 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs